The underestimated relevance and value of vocational education in tertiary education : making the invisible visible - Hippach-Schneider, Ute [Verfasser]; Schneider, Verena [Verfasser]; Ménard, Boris [Verfasser]; Tritscher-Archan, Sabine [Verfasser] (My University, 2017)
"Increasing the number of tertiary graduates has been a priority on the political agenda of the EU for some years. The focus has mainly been on academic courses though, with less emphasis on the role of vocational education and training. International educational statistics indeed show a clear increase in the number of persons completing tertiary education programmes in recent years. In overall terms, this development is referred to as 'academisation'. The present paper provides a critical analysis and uses examples from Germany, Austria and France to show that this interpretation is neglecting two crucial facts. One is that various academic programmes in fact are combining academic with vocational learning. The other is that there are vocational programmes in the tertiary education sector that are not adequately visible in international education statistics. This understanding is important in relation to future policy-making as well as individual decision-making." (authors' abstract; BIBB-Doku)
Keywords: G 1.2.3 Qualifikationsentwicklungen; T 3.5 Statistik; I 2.1 Deutschland; I 2.2.1 Westeuropa; Höhere Berufsbildung; Akademisierung; Berufsbildung; Bildungsstatistik; ISCED; Internationaler Vergleich; Bundesrepublik Deutschland; Österreich; Frankreich